Stuart Woods' Finders keepers [large type] - Battles, Brett (Woods, Stuart. Stone Barrington novel, 2025)
"After attending an Arrington properties meeting on Martha's Vineyard at the group's newest location, The Vineyard Arrington, Stone Barrington returns to New York City to catch up with his old friend Jack Coulter over lunch, who requests Stone's help in settling his niece Sara into city life post-divorce. Always one to please, Stone takes Sara under his wing. But when various men from Sara's past startgetting hurt, and Jack's loved ones find themselves a target in a deadly scheme, it's up to Stone to put the pieces together--before the shrouded conspirer manages to tear them all apart, permanently"--